2013
DOI: 10.1177/2047487313514895
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiovascular mortality associated with gout: a systematic review and meta-analysis

Abstract: BackgroundHyperuricaemia, the biochemical precursor to gout, has been shown to be an independent risk factor for mortality from cardiovascular disease (CVD), although studies examining the clinical phenomenon of gout and risk of CVD mortality report conflicting results. This study aimed to produce a pooled estimate of risk of mortality from cardiovascular disease in patients with gout.DesignSystematic review and meta-analysis.MethodsElectronic bibliographic databases were searched from inception to November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 39 publications
5
86
0
5
Order By: Relevance
“…In line with this, a prospective study of the Health Professionals Follow‐Up Study confirmed these data by also revealing an ≈60% increase in the risk of fatal coronary heart disease in men with diagnosed gout and a history of CVD 3. Additional new independent meta‐analyses have confirmed these correlations of gout and CVD risk 7, 8. However, the most conclusive studies have only been conducted in men, most likely because risk factors and development of gout in women follow different patterns since serum estrogen levels play a significant role in the control of uric acid levels.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In line with this, a prospective study of the Health Professionals Follow‐Up Study confirmed these data by also revealing an ≈60% increase in the risk of fatal coronary heart disease in men with diagnosed gout and a history of CVD 3. Additional new independent meta‐analyses have confirmed these correlations of gout and CVD risk 7, 8. However, the most conclusive studies have only been conducted in men, most likely because risk factors and development of gout in women follow different patterns since serum estrogen levels play a significant role in the control of uric acid levels.…”
Section: Introductionsupporting
confidence: 59%
“…Because CVD and coronary heart disease/CAD comprise slightly different diseases and none of the studies described above gave details on the specific type of coronary heart disease, it would have been very interesting to differentially display the data presented by Pagidipati et al for sex and race since ≈300 individuals with a gout history included in this study were women and/or of nonwhite background. Association between MI and gout is less clear7; however, recent studies and meta‐analysis suggest a correlation of gout and the risk for nonfatal MI in both sexes,13, 14, 15 a finding not supported by data from Pagidipati et al 4. Yet, comparison between different studies in general has to be viewed with caution.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have previously demonstrated an increased risk of CVD death associated with gout,6, 7 and a meta‐analysis of 6 studies revealed a 29% increase in CVD mortality (95% CI, 1.14–1.44) 9. However, these analyses examined individuals without known CAD.…”
Section: Discussionmentioning
confidence: 99%
“…nflammatory rheumatologic disorders such as rheumatoid arthritis, 1,2 systemic lupus erythematosus, 2,3 gout, 4 psoriatic arthritis 2,5 and ankylosing spondylitis 2,6 are associated with an increased risk of vascular disease, especially cardiovascular disease, leading to substantial morbidity and premature death. [2][3][4][5][6] Recognition of this excess vascular risk has led to management guidelines advocating screening for and management of vascular risk factors.…”
mentioning
confidence: 99%